2016
DOI: 10.1186/s12957-016-0895-4
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoplasty using continuous suture in complete monitor view: a suitable method of thoracoscopic sleeve lobectomy for non-small cell lung cancer

Abstract: BackgroundOur study aims to determine the value of bronchial anastomosis using complete continuous suture.MethodsSix patients diagnosed with central lung carcinoma who were candidates for right-sided sleeve lobectomy and underwent sleeve resection of the right upper lobe by thoracoscopic surgical procedure.ResultsThe mean surgical time was 182 min (range, 110 to 260 min). The mean time of bronchial anastomosis was 49 min (range, 18 to 76 min). The mean bleeding was 110 mL (range, 50 to 260 mL). Median chest tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
(3 reference statements)
0
4
0
2
Order By: Relevance
“…Here, the level of evidence in the literature is limited to a few small series. 4 We describe the use of a barbed suture. Due to the memory effect of the suture, the alleged disadvantage of the missing tactile feedback can easily be compensated.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the level of evidence in the literature is limited to a few small series. 4 We describe the use of a barbed suture. Due to the memory effect of the suture, the alleged disadvantage of the missing tactile feedback can easily be compensated.…”
Section: Discussionmentioning
confidence: 99%
“…Although no randomized trials have been performed on this topic and only few case reports have been published, all authors agree that the most important factor influencing the outcomes of such a complex thoracoscopic procedure is the Endoscopic bronchial and tracheal anastomosis methods include intermittent, continuous, and continuous mixed with intermittent sutures (58)(59)(60)(61)(62)(63)(64). When performing a thoracoscopic procedure, most of authors agree on the usefulness of a complete continuous suture starting from the posterior part of the anastomosis to the anterior one, since it offers a clear operative view (53)(54)(55)(56)(57)(65)(66)(67).…”
Section: Tumors >7 CMmentioning
confidence: 99%
“…In 2002, Santambrogio et al (8) reported the first case Other retrospective studies (10,11) have reported on the benefits of video-assisted thoracoscopic multiportal and uniportal VATS lobectomy and sleeve resection compared with those of thoracotomy and lobectomy (especially sleeve resection), including reduced surgical trauma, less incisional pain, lower incidence of postoperative complication, shorter hospital stay, and earlier recovery to start adjuvant therapies (12,13). Yan et al (14) reported the criteria of the European Society of Thoracic Surgeons (ESTS) consensus on multiportal VATS lobectomy as: "No use of rib-spreading; Utility incision with a maximum length of 8 cm to deliver the specimen; Individual dissection of the vein, arteries and airway for the lobe; Standard lymph node sampling or dissection", while the consensus on the criteria for uniportal VATS lobectomy as reported by Bertolaccini et al (15) were reported as: "The maximum size of the incision should be ≤4 cm in the anterior or middle-anterior axillary line; Eligibility for VATS lobectomy should include tumors in T1/T2 and N0/N1 status; Chest wall involvement was not considered an absolute contraindication for VATS lobectomy, whereas a hilar tumor was considered a relative contraindication.…”
Section: Commentsmentioning
confidence: 99%